PENGARUH MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN BERPIKIR KOGNITIF DAN AFEKTIF SISWA SEKOLAH DASAR - Zusmar, Elvi Zusmar; Witarsa, Ramdhan; Masrul, Masrul (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
The realistic mathematics education learning model is one of the appropriate learning models to be applied in elementary schools. This research aims to measure how much influence the realistic mathematics education learning model has on the cognitive and affective thinking skills of elementary school students. The method used in this research is quasi-experimental method. This method has nine stages, namely: literature review, identifying and limiting research problems, developing research hypotheses, creating research designs, conducting pretests, conducting experiments, conducting post-tests, processing and analyzing data, and drawing conclusions. The research sample amounted to 28 students, consisting of 14 students in the experimental class and 14 students in the control class. The data collection technique used was a test of students' cognitive and affective thinking skills. The results showed that the application of the realistic mathematics education learning model had a significant effect on the cognitive and affective thinking skills of elementary school students in the experimental class. Other cognitive and affective thinking skills can be further researched in order to get broader findings.